2019
DOI: 10.2514/1.a34182
|View full text |Cite
|
Sign up to set email alerts
|

Architectural Optimization Framework for Earth-Observing Heterogeneous Constellations: Marine Weather Forecast Case

Abstract: Earth observation satellite programs are currently facing, for some applications, the need to deliver hourly revisit times, sub-kilometric spatial resolutions and near-real-time data access times. These stringent requirements, combined with the consolidation of small-satellite platforms and novel distributed architecture approaches, are stressing the need to study the design of new, heterogeneous and heavily networked satellite systems that can potentially replace or complement traditional space assets. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Iso-score curves are projected in the surface to ease the analysis of the plot and highlight the effects of constellation sizes in architectural scores. The clear identification of plateaus for sizes larger than 24 satellites suggests that these designs are worsened by excessive cost and/or some of the ilities modeled in this case [27]. The green markers locate the most promising regions of the design space.…”
Section: Design Space Exploration and Architectural Trendsmentioning
confidence: 98%
See 3 more Smart Citations
“…Iso-score curves are projected in the surface to ease the analysis of the plot and highlight the effects of constellation sizes in architectural scores. The clear identification of plateaus for sizes larger than 24 satellites suggests that these designs are worsened by excessive cost and/or some of the ilities modeled in this case [27]. The green markers locate the most promising regions of the design space.…”
Section: Design Space Exploration and Architectural Trendsmentioning
confidence: 98%
“…The pre-selection was guided by a careful inspection of differences and similarities among solutions of higher ranks. The analysis of coarse performance metrics, detailed in [27], showed that amongst the 100 solutions of highest score the SAR-X and the Optical imager were critical to provide acceptable spatial resolutions and revisit times for some of the measurements of this use case. Due to their mass and power requirements, these instruments can only fly in heavy platforms, which also present a significant cost compared to medium and small satellite designs.…”
Section: Design Space Exploration and Architectural Trendsmentioning
confidence: 99%
See 2 more Smart Citations
“…Paras et al pointed out that the selection of statistical indicators such as moving average, skewness and kurtosis coefficient can extract hidden trends in meteorological changes, which can be used as model features. And pointed out that the weather forecast based on the neural network method can produce good results, which can be considered as an alternative to the traditional meteorological method[15][16] .…”
mentioning
confidence: 99%